Structure of aqueous electrolyte solutions near a hydrophobic surface - Kinoshita, M. (Condensed Matter Physics, 2007)
The structure of aqueous solutions of 1:1 salts (KCl, NaCl, KF, and CsI) near a hydrophobic surface is analysed using the angle-dependent integral equation theory. Water molecules are taken to be hard spheres imbedded with multipolar moments including terms up to octupole order, and hard spherical ions are immersed
in this model water. The many-body interactions associated with molecular polarizability are treated at the self-consistent mean field level. The effects of cationic and anionic sizes and salt concentration in the bulk are discussed in detail. As the salt concentration increases, the layer of water molecules next to the surface becomes denser but its orientational order remains almost unchanged. The concentration of each ion
at the surface can be drastically different from that in the bulk. As a striking example, at sufficiently low salt concentrations, the concentration of I⁻ is about 500 times higher than that of F⁻ at the surface. Структура водних розчинiв 1:1 солей (KCl, NaCl, KF, i CsI) поблизу гiдрофобної поверхнi аналiзується в рамках теорiї i орiєнтовно залежних iнтегральних рiвнянь. Молекули води розглядаються як твердi сфери з вставленими мультипольними моментами включно до октупольного момента. Твердi сферичнi iони помiщенi в цю модель води. Багаточастинковi взаємодiї, обумовленi молекулярною поляризованiстю, трактуються на рiвнi самоузгодженого середнього поля. Детально обговорюються ефекти катiонних та анiонних розмiрiв i концентрацiй солi в об’ємi . Iз зростанням концентрацiї солi шари молекул води бiля поверхнi стають густiшими, але їх орiєнтацiйний порядок залишається майже незмiнним. Концентрацiя кожного з iонiв бiля поверхнi може бути суттєво iншою, нiж в об’ємi. Як вражаючий приклад, при достатньо низьких концентрацiях солi, концентрацiя I⁻ бiля поверхнi майже в 500 раз вища, нiж концентрацiя F⁻.